High-pressure processing effectively controls Proteus mirabilis and prevents histamine formation in low-salt semi-dried giant catfish - Muhamad Amin; Suriya Palamae; Sabri Mohd Ali; Soottawat Benjakul (Food Control, 2026)

Large-scale microtremor analysis and lineament mapping for evaluating geological hazards in reservoir-induced seismicity regions: The case history of Kenyir Geopark - Susie Cahyanti Tasman; Neeran Niraj; Muhammad Noor Hisyam Jusoh; Abdul Halim Abdul Latiff; Siti Nur Fathiyah Jamaludin; Muhd Nur Ismail Abdul Rahman; Rudiyanto; Muhammad Afiq Md Ali; Muhamad Zaki Zulkifli; Yuzwan Mohamad; Kee Soo Chen; Fawwaz Azfar Abd Ghafar; et al. (Journal of Applied Geophysics, 2026)

Drought frequency and spatial variability in the Kelantan River Basin: comparative evaluation of SPI and EDI - Muhamad Hazim Solahudin; Jing Lin Ng; Yuk Feng Huang; Swee Pin Yeap; Ali Najah Ahmed; Majid Mirzaei; Fatemehsadat Mortazavizadeh; Zi Qing Lee (Theoretical and Applied Climatology, 2026)

Climate change and global energy transformation: The role of renewable energy and electric vehicles - Ali Q. Al-Shetwi; Muhamad Zahim Sujod; Khaled A. Mahafzah; Ahmad Abuelrub; Hussein M.K. Al-Masri; M.A. Hannan (Science of The Total Environment, 2026)

Prevalence and mechanisms of antimicrobial resistance in respiratory bacterial pathogens of ruminants: a systematic review - Sophia Peter; Muhammad Zaki Zulkiffle; Bura Paul Thlama; Muhamad Hakim Mohd Ali Hanafiah; Faez Firdaus Jesse Abdullah; Juriah Kamaludeen; Suhaili Mustafa (Veterinary Research Communications, 2026)

Integrating multi-scale precipitation variability into ensemble modeling using maximum overlap discrete wavelet transform for improved drought projections under emission scenarios - Hussnain Abbas; Zulfiqar Ali; Muhamad Shakeel; Muhamad Mohsin; Amna Nazeer; Sadia Qamar (Theoretical and Applied Climatology, 2026)

Real-time ultrasound and RGB imaging integration for non-invasive prediction of ribeye area in Tropical Crossbred Brahman Cattle - Nurul Nuraliya Shahrai; Salma Mohamad Yusop; Maimunah Mohd Ali; Mohd Hanis Mohd Saim; Ahmad Rodzian Pok Abdul Aziz; Muhamad Hidayat Mohd Hashim; Shuji Ueda (Tropical Animal Health and Production, 2026)

State of sustainability assessments of metal additive manufacturing: literature review and triple-bottom-line perspectives - Nur Safirah Bahuriddin; Muhamad Zameri Mat Saman; Nurhasyimah Mohamad-Ali; Nor Hasrul Akhmal Ngadiman; Muhd Ikmal Isyraf Mohd Maulana (Environmental Science and Pollution Research, 2025)
With growing global energy and climate concerns, metal additive manufacturing (AM) has emerged as an innovative solution, offering various advantages, particularly in minimizing environmental effects. However, the sustainability assessment of metal AM, in particular, environmental, economic, and social impacts under the triple-bottom-line (TBL) has not been adequately communicated to guarantee high-quality outcomes. This study reviews emerging sustainability assessment of metal AM, focusing on papers addressing multiple sustainability dimensions. Several parameters are critically analyzed, including sustainability dimensions, sustainability indicators, circular economy domain, life cycle stages, metal AM technology, and others. The findings indicate that life cycle assessment and life cycle costing are the most commonly used methods; however, both are applied independently, with no effort to integrate them into a single sustainability score. Besides, the environmental dimension is the primary consideration, while the economic and social dimension lacks sufficient exploration. From the perspective of life cycle stages, the AM stage is the primary focus within the system boundary, whereas the design, use and end-of-life stages are underrepresented. Resource efficiency is covered within the circular economy domain, while recycling, a fundamental aspect of metal AM with considerable potential, remains overlooked. This study serves as a valuable reference to enhance the inclusivity of sustainability assessments of metal AM, focusing on integrating TBL, life cycle stages, indicator reliability and recycling aspects.

Optimization of ternary glutaric acid-based deep eutectic solvents (TGADES) for oxidative-extractive desulfurization of model oil using response surface methodology (RSM) - Muhamad Iqbal Ishak; Asiah Nusaibah Masri; Azad Anugerah Ali Rasol; Izni Mariah Ibrahim; Hasrinah Hasbullah (Sustainable Chemistry and Pharmacy, 2025)

Evaluation of the potential of replanted rubber wood and palm oil waste with coal as co-combustion fuels in a lab-scale combustion simulator: ash deposition aspects - Hariana Hariana; Adi Prismantoko; Suyatno Suyatno; Hafizh Ghazidin; Fairuz Milkiy Kuswa; Ade Sana Ruhiyat; Cuk Supriyadi Ali Nandar; Muhamad Iqbal Felani; Widi Pancono; Unggul Priyanto; Kusmiyati Kusmiyati; Hari B. Vuthaluru (Biomass and Bioenergy, 2025)

Design, synthesis, and computational analysis (molecular docking, DFT, MEP, RDG, ELF) of diazepine and oxazepine sulfonamides: biological evaluation for in vitro and in vivo anti-inflammatory, antimicrobial, and cytotoxicity predictions - Sangar Ali Hassan; Dara Muhammed Aziz; Dana Ali Kader; Shwana Muhamad Rasul; Meer Ali Muhamad; Alla Ahmad Muhammedamin (Molecular Diversity, 2025)

Marine landscape mapping for ecologically relevant habitat suitability modelling - Bryan Yong; Khaira Ismail; Azizi Ali; Rozaimi Che Hasan; Muhammad Abdul Hakim Muhamad (Earth Science Informatics, 2025)

Recent advances in recycling and upcycling of hazardous plastic waste: A review - Siti Zulaika Khairul Anuar; Abu Hassan Nordin; Siti Muhamad Nur Husna; Abdul Hafidz Yusoff; Syafikah Huda Paiman; Siti Fadilla Md Noor; Muhammad Luqman Nordin; Siti Nurlia Ali; Ya Mohammad Nazir Syah Ismail (Journal of Environmental Management, 2025)

Gut microbiota and functional metabolic predictions in white feces disease-infected Pacific white shrimp, Penaeus vannamei, from Indonesian farms - Muhamad Amin; Karina Kristanti Ekarani Rahardjo; Alief Erwaanda Panosa; Woro H. Satyantini; Akhmad Taufiq Mukti; Muhamad Ali; Laila Musdalifah; Halil Akhyar; Uun Yanuhar; Mohammad Noor Amal Azmai; Takaomi Arai (Fish & Shellfish Immunology, 2025)

Numerical investigation of hydrogen-diesel dual fuel engine: Combustion and emissions characteristics under varying hydrogen concentration and exhaust gas recirculation - Mohamed Ali Abuelnour; Mohd Farid Muhamad Said; Abuelnuor A.A. Abuelnuor (Fuel, 2024)

Identification of NO2 and SO2 over China: Characterization of polluted and hotspots Provinces - Md. Arfan Ali; Mazen E. Assiri; M. Nazrul Islam; Muhamad Bilal; Ayman Ghulam; Zhongwei Huang (Air Quality, Atmosphere & Health, 2024)

Assessment of pilot-scale sewage sludge pelletization for non-food crop fertilization: nutrient content, pathogenicity, and growth performance - Mohd Hafif Samsudin; Mohd Zulkhairi Mohd Yusoff; Mohd Ali Hassan; Mohd Rafein Zakaria; Ahmad Muhaimin Roslan; Siti Suliza Salamat; Muhamad Yusuf Hasan; Mohd Huzairi Mohd Zainudin; Mohammed Abdillah Ahmad Farid; Yoshihito Shirai (Environmental Monitoring and Assessment, 2024)

Analyzing Agricultural Land Use with Cellular Automata-MARCOV and Forecasting Future Marine Water Quality Index: A Case Study in East Coast Peninsular Malaysia - Mohd Saiful Samsudin; Azman Azid; Muhammad Amar Zaudi; Mohd Ridhwan Adam; Muhamad Shirwan Abdullah Sani; Shazlyn Millenana Saharuddin; Aminu Ibrahim; Mohd Fahmi Mohd Nasir; Mou Leong Tan; Nurul Izzati Mohd Ali (Water, Air, & Soil Pollution, 2024)

Structure and Diversity of Microbiomes Associated with the Gastrointestinal Tracts of Wild Spiny Lobsters and Profiling Their Potential Probiotic Properties Using eDNA Metabarcoding - Muhamad Amin; Hussein Taha; Laila Musdalifah; Muhamad Ali; Alimuddin Alimuddin; Sahrul Alim; Takaomi Arai (Fishes, 2024)
Microbial communities have been documented as playing many pivotal roles, and contributing to the growth or health performance of animal hosts. Thus, many studies are currently looking for potential beneficial bacteria “probiotics” from diverse environments, including wild species. The present study aimed to investigate the diversity and potential metabolic functions of bacterial communities in the gastrointestinal tract of wild spiny lobsters. The gastrointestinal (GI) tracts of two wild lobster species (Panulirus ornatus and Panulirus homarus) were dissected aseptically and analyzed through high-throughput sequencing, followed by PICRUSt analysis. The results exposed that the most dominant phyla inhabiting both lobster species at the post-puerulus and juvenile stages were Proteobacteria, Firmicutes, Bacteriodota, Patescibacteria, and Verrucomicrobiota, while at the genus level, the GI tracts were mostly dominated by Photobacterium, Candidatus Bacillopora, Vibrio, and Catenococcus at the post-peurulus stage, and Vibrio, Catenococcus, Acanthopleuribacter, Acinetobacter, Pseudoalteromonas, Grimontia, and Photobacterium at the juvenile stage. Further metagenomic prediction analysis discovers many potential probiont properties indicated by the detection of marker genes corresponding to many important metabolic activities, such as antimicrobial compounds (streptomycin, vancomycin, carbapenem, tetracycline, novobiocin, penicillin, cephalosporin, ansamycines, butirosin, and neomycin), antioxidants (e.g., flavonoids and carotenoids), and several important digestive enzymes (e.g., lipase, protease, and amylase). These results suggest that GI tracts of wild spiny lobsters are potential sources to discover novel probionts for aquaculture purposes. Further studies, such as the isolation of the natural product-producing bacteria, or cloning of the beneficial compound-identified genes, are highly recommended to develop novel probiotic strains for aquaculture purposes.

A model for end-of-life recovery in the automotive sector in Malaysia - Nurhasyimah Mohamad-Ali; Muhamad Zameri Mat Saman; Raja Ariffin Raja Ghazilla (Sustainable Production and Consumption, 2024)

One-way fluid structure interaction analysis of a static savonius hydrokinetic turbine under different velocity and surface roughness with different blade materials - Muhamad Hasfanizam Mat Yazik; Mohd Hafiz Zawawi; Ali Najah Ahmed; Lariyah Mohd Sidek; Hidayah Basri; Farzad Ismail (Ocean Engineering, 2024)

Impact of elicitors (alginate, Bacillus cereus, and cholesterol) on the production of secondary metabolite (lovastatin, (+)-geodin, and sulochrin) by Aspergillus terreus ATCC 20542 during submerged fermentation - Nurul Solehah Mohd Zaini; Hanan Hasan; Ali Abbas; Alejandro Montoya; Muhamad Hafiz Abd Rahim (Biocatalysis and Agricultural Biotechnology, 2024)

Tailored nanofibrous molecularly imprinted polymers for selective removal of di(2-ethylhexyl) phthalate: A computer-aided design and synthesis approach - Nurrahmi Handayani; Yanuar Setiadi; Siti Oryza Sativa; Aria Pinandita; Muhamad Allan Serunting; Untung Triadhi; Muhamad Nasir; Muhammad Ali Zulfikar (Journal of Water Process Engineering, 2023)

The structure, composition, and predicted microbiome functional genes in Pacific white shrimp (Litopenaeus vannamei) grow-out ponds with different survival rates through high-throughput sequencing - Muhamad Amin; Yoga Pramujisunu; Ni Kadek Dita Cahyani; Akhmad Taufiq Mukti; Mirni Lamid; Muhamad Ali; Orhan Tufan Eroldoğan (Aquatic Sciences, 2023)

Association between dietary 3-monochloropropane-1,2-diol esters (3-MCPDE) and renal cancer in Peninsular Malaysia: exposure assessment and matched case-control study - Siti Hajar Muhamad Rosli; Mei Siu Lau; Tasnim Khalid; Siti Khuzaimah Maarof; Suganthi Jeyabalan; Syazwani Sirdar Ali; Norhayati Mustafa Khalid; Mohd Fairulnizal Md Noh; Ruhaya Salleh; Lalitha Palaniveloo; Mohamad Hasnan Ahmad; Nurul Izzah Ahmad; et al. (Food Additives & Contaminants: Part A, 2023)

Side-Scan Sonar Coupled with Scuba Diving Observation for Enhanced Monitoring of Benthic Artificial Reefs along the Coast of Terengganu, Peninsular Malaysia - Azizi Ali; Muhammad Ruzi Abdullah; Che Din Mohd Safuan; Aminudin Muhammad Afiq-Firdaus; Zainudin Bachok; Mohd Fadzil Mohd Akhir; Roslan Latif; Azri Muhamad; Tan Hock Seng; Adina Roslee; Khaira Ismail (Journal of Marine Science and Engineering, 2022)
Since the 1970s, artificial reef (AR) deployment has been one of the common approaches to augment the local production of coastal fish in Malaysia. However, there is a lack of strategy to assess and evaluate the success of pre-deployed AR. Realizing the need for an effective qualitative and quantitative monitoring and evaluation of AR, this study proposes side-scan sonar coupled with scuba diving observation for the enhanced monitoring of pre-deployed Bioceramic Korean (BK) AR along the coast of Terengganu, Peninsular Malaysia. This method employs an integrated side-scan sonar with a data acquisition system for the detection of the precise location of the BK AR which were deployed at Tukun Telaga Batin off the Terengganu coastline in 2003 by the Fisheries Development Authority of Malaysia (FDAM). Following the determination of the exact location of three BK AR areas, a scuba diving team was sent to survey the physical conditions of the AR and assess the feasibility of the AR as an artificial habitat for marine life. The scan sonar images were compared with the captured photographs and videos acquired during the scuba diving session for a comprehensive value-added assessment. The collected data from the scuba diving session were also processed to measure the fish diversity, the fish biomass, and identify the fish community surrounding the AR. Based on the results, the BK AR remained in extremely good condition, physically intact, without significant breakage or damage, and with no major subsidence into the sediment after 19 years of deployment. A total of 108 BK AR modules were detected in three large groups using the mosaicked sonar images. Following cross-examination to validate the AR measurements using the AR’s shadows on the seafloor, the height of the BK AR consistently ranged from 1.7 m to 1.8 m. In addition, 34 species of fish from 14 families and 26 genera were identified, with most species classified as reef-associated (RA) fish with a biomass value of 1173.31 ± 1136.69 kg m−3, indicating the successfulness of the BK AR as fish-aggregating devices (FADs). The growth of hard corals on top of the bioceramic plate of the AR module further supported the diversified community of marine life surrounding the BK AR. In conclusion, the side-scan sonar coupled with scuba diving observation demonstrates an effective qualitative and quantitative technique for the monitoring and evaluation of pre-deployed AR. This strategy is recommended to be utilized to determine the success of pre-deployment AR.

Isolation and characterization of acid-tolerant Stichococcus-like Microalga (Tetratostichococcus sp. P1) from a tropical peatland in Malaysia - Eri Sahabudin; Jinwoong Lee; Ryo Asada; Ezzah Atikah Marsid; Nurtasbiyah Yusof; Nurul Syazwani Ahmad Sabri; Hani Susanti; Muhamad Ali Muhammad Yuzir; Fazrena Nadia Md Akhir; Nor’azizi Othman; Zuriati Zakaria; Kengo Suzuki; et al. (Journal of Applied Phycology, 2022)

The impact of SARS-CoV-2 treatment on the cardiovascular system: an updated review - Mohammed Ahmed Akkaif; Abubakar Sha’aban; Arturo Cesaro; Ammar Ali Saleh Jaber; Andrea Vergara; Ismaeel Yunusa; Abubakar Ibrahim Jatau; Mustapha Mohammed; G. Saravana Govindasamy; Majed Ahmed Al-Mansoub; Muhamad Ali Sheikh Abdul Kader; Baharudin Ibrahim (Inflammopharmacology, 2022)

Molybdenum-Induced Effects on Grain Yield, Macro–micro-nutrient Uptake, and Allocation in Mo-Inefficient Winter Wheat - Mohamed G. Moussa; Xuecheng Sun; Marwa A. Ismael; Ali Mohamed Elyamine; Muhammad Shoaib Rana; Muhamad Syaifudin; Chengxiao Hu (Journal of Plant Growth Regulation, 2022)

Organic acid and probiotic derived from grass silage improved egg quality in Pegagan laying duck: a research note - Sofia Sandi; Meisji L. Sari; Fitra Yosi; Eli Sahara; Bella P. Maharani; Asmak Asmak; Muhamad N. Rofiq; Asep I. M. Ali (Tropical Animal Health and Production, 2022)

RETRACTED ARTICLE: Property market price response to flood-hazard - Muhammad Najib Razali; Siti Hafsah Zulkarnain; Zakri Tarmidi; Nurul Hana Adi Maimun; Yasmin Mohd. Adnan; Muhamad Ali Yuzir (Natural Hazards, 2020)

Detection of koi herpesvirus in healthy common carps, Cyprinus carpio L. - Muhamad Amin; Dian N. Adrianti; Ni Luh A. Lasmika; Muhamad Ali (VirusDisease, 2018)

Raingauge network optimization in a tropical urban area by coupling cross-validation with the geostatistical technique - Mohd Zaharifudin Muhamad Ali; Faridah Othman (Hydrological Sciences Journal, 2018)

Removal of Remazol Brilliant Blue R from Aqueous Solution by Adsorption Using Pineapple Leaf Powder and Lime Peel Powder - Normaizatul Akmar Rahmat; Aili Aqilah Ali; Salmiati; Nafsiah Hussain; Mimi Suliza Muhamad; Risky Ayu Kristanti; Tony Hadibarata (Water, Air, & Soil Pollution, 2016)